A review on biological recycling in agricultural waste-based biohydrogen production: Recent developments. (March 2022) - Zheng, Yaping; Zhang, Quanguo; Zhang, Zhiping; Jing, Yanyan; Hu, Jianjun; He, Chao; Lu, Chaoyang
Highlights: Relevant aspects for biohydrogen production from agricultural wastes were reviewed. The structure and pretreatment methods of agricultural wastes were discussed. Means and affecting factors of biohydrogen production were presented. Opportunities and challenges in waste-based biohydrogen production were discussed. Abstract: Hydrogen has become a research highlight by virtue of its clean energy production technology and high energy content. The technology of biohydrogen production from biological waste via fermentation has lower costs, provides environment-friendly methods regarding energy balance, and creates a pathway for sustainable utilization of massive agricultural waste. However, biohydrogen production is generally limited by lower productivity. Many studies have been conducted aimed at improving biohydrogen production efficiency. Hence, this review is intended to describe improving routes for biohydrogen production from agricultural waste and highlights recent advances in these approaches. In addition, the critical factors affecting biohydrogen production, including the pretreatment method, substrate resource, fermentation conditions, and bioreactor design, were also comprehensively discussed along with challenges and future prospects.